(untitled) (Research, Society and Development, 2022)
The aim of this work was to evaluate the antifungal activity of essential oils (EOs) of Lippia gracilis and Lippia sidoides accessions, their major compounds and nanoemulsions. Nanoemulsions with 18% of EO or major compound were produced by spontaneous emulsification method. The EO of two L. gracilis accessions (LGRA-106 and LGRA-109) and two L. sidoides accessions (LSID-102 and LSID-104) were extracted by hydrodistillation and the major compounds thymol and carvacrol were purchased commercially. Antifungal activity was tested against Lasiodiplodia theobromae by calculating the percentage of inhibition of mycelial growth caused by different concentrations (0.1, 0.5, 1.0, 5.0, and 10.0 mL.L-1), in relation to the control. The EOs and their respective nanoemulsions presented as major compounds thymol (LGRA-106: 61.84% and Nano-106: 63.43%; LSID-102: 64.07% and Nano-102: 83.03%) or carvacrol (LGRA-109: 54.56% and Nano-109: 45.63%; LSID-104: 69.06% and Nano-104: 38.66%). Nano-104 presented 35.91% of an unidentified compound. The fungicidal activity of the EOs was similar to that of the major compounds, with a minimum fungicidal concentration of 1.0 mL.L-1 for LGRA-106, LSID-102 as well as for thymol, and 0.5 mL.L-1 for LGRA-109, LSID-104 as well as for carvacrol. The nanoemulsions were only able to reduce the mycelial growth of the fungus except for Nano-104 that exhibited fungicidal activity at the concentration of 10 ml.L-1. It was possible to observe that the EOs exhibited greater toxicity against L. theobromae than the nanoemulsions. These results can help in the development of products for the control of this important phytopathogen.